Sulfate Amelioration Of Chromium Toxicity On Water Spinach ( Ipomoea Reptans Poir.) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
ABSTRACT Kasmiyati, S. & Santosa 2000. Sulfate amelioration of chromium toxicity on water spinach ( Ipomoea reptans Poir.). Biologi2 (10): 599-613. A study was conducted to assess the effects of sulfate addition on chromium toxicity of Ipomoea reptans Poir., using modified physiological respons indicators. Plants were hydroponically grown on sand culture with 10% strength Hoagland nutrient solution. Combination of five levels of sulfate concentration i.e. : 192.2-384.5-768.9-- 9612 and 19215 mg SO:- /1 respectively and three levels of chromium concentration i.e. : 0.0 - 5.0 - and 10.0 mg CrOp /1 respectively were simultaneously added. The physiological responses measured were plant growth, leaf nitrate reductase activity, leaf protein and chromium accumulation. The results showed that chromate inhibited the growth of plants, but increased nitrate reductase activity and protein content in the leaf. Chromium accumulation was higher in the roots than in the leaves. Accumulation of chromium in the leaf reduced the production of photosynthetic pigment (chlorophyll a, chlorophyll b and carotenoid). Addition of sulfate increased plants growth, photosynthetic pigment and leaf protein content of chromate-treated plant. Sulfate addition reduced chromium accumulation in the chromate-treated plant roots with high chromate (10 mg/1) and in the chromate-treated plant leaves with low chromate (5 mg/1). The results proved that sulfate has potentiality to reduce the effects of chromium toxicity on the growth of L reptans Poir.